Effect of the spirobiindane group in sulfonated poly(arylene ether sulfone) copolymer as electrode binder for polymer electrolyte membrane fuel cells - Chae, Ji Eon; Kim, Bo Hyun; Noh, Jee Hyun; Jung, Jaewoo; Kim, Jin-Young; Jang, Jong Hyun; Yoo, Sung Jong; Kim, Hyoung-Juhn; Lee, So Young (한국공업화학회, 2017)
Electrode properties determine the membrane-electrode assembly (MEA) performance of fuel cells and are influenced by the materials and processing. A high-performance electrode requires good adhesion between the membrane and catalyst, excellent gas permeability, and good ion conduction. Here, sulfonated poly(arylene ether sulfone) (SPAES) containing a bulky spirobiindane (Spiro) group is proposed as a new hydrocarbon electrode binder for MEAs. The effect of the Spiro group on MEA performance was compared to that of the common biphenylsulfone. The structural differences between the two binders affected the mass transport region of the current-voltage polarization (related to gas permeation). The spiro-polyethersulfone (PES) had 115 times higher 02 permeability (30 Barrer) than that of PES. From H-1 NMR spectra, the degree of sulfonation (DS) of each SPAES was confirmed, where the proton conductivity of Spiro 30, Spiro 20, and BPS 30 were 28.2, 10.1, and 26.9 mS cm(-1), respectively. In addition, the DS of the electrode binder contributed to the Ohmic region of the i-V curve. The Ohmic resistance of these hydrocarbon binders was similar to that of commercial Nafion binder (0.13-0.15 Omega cm(2)). However, the charge transfer resistance of our binders was higher than that of Nafion due to insufficient gas permeability and low proton conductivity. (C) 2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.